(untitled) (Indian Journal of Public Health Research & Development, 2020)
Brucella abortus is a zoonotic pathogen bacteria which can cause brucellosis commonly known as undulant fever in human and abortion in cattle. VirB4 is one of the virulence factor that cause these bacteria became pathogen during infection period. Molecular characterization was performed by using Polymerase Chain Reaction (PCR) for further understand within antigens involved in the virulence or the immune system, genetic and immunologic characterization of a VirB4 protein which play role as virulence factor. Local isolate of B. abortus that were already obtained were cultured on Brucella agar media. Subsequently, the PCR results were performed running in a 1% of agarose gel and can be visualized with the aid of UV transluminator. DNA sequencing of VirB4 protein B. abortus of local isolates was performed using PCR and primer products that were positive in amplification. The examination results showed that encoding genes of the VirB4 protein using PCR molecular examination had positive bands with an 1600 bp amplicon length. This present study are expected to provide scientific information on the characterization of VirB4 protein as virulence factor of B. abortus local isolates in the medical field and can be developed and applied as a diagnostic kit for controlling brucellosis.